2nd Aeroacoustics Conference 1975
DOI: 10.2514/6.1975-523
|View full text |Cite
|
Sign up to set email alerts
|

Further experimental results on the structure and acoustics of turbulent jet flames

Abstract: The structure of open turbulent jet flames is experimentally studied in the context of their noise emission characteristics. The differences between premixed and (co-flow) non-premixed flames are explored. Recent experiments repeated in an anechoic chamber complement earlier results obtained in a hard-walled bay. The reactants (methane and enriched air) are burned in the premixed, or non-premixed, mode after a length of pipe flow (t/D> 150). The thick-walled tubes anchor the flames to the tip at all of the vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…It is also generally experimentally observed that flame noise levels peak in the frequency range 200-1000 Hz [6,11]. Some data also indicate the presence of multiple peaks in the acoustic spectra [12]. A number of analyses have assumed a Strouhal number scaling (based on burner diameter and jet exit velocity) for this peak frequency [12,13].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is also generally experimentally observed that flame noise levels peak in the frequency range 200-1000 Hz [6,11]. Some data also indicate the presence of multiple peaks in the acoustic spectra [12]. A number of analyses have assumed a Strouhal number scaling (based on burner diameter and jet exit velocity) for this peak frequency [12,13].…”
Section: Introductionmentioning
confidence: 97%
“…Some data also indicate the presence of multiple peaks in the acoustic spectra [12]. A number of analyses have assumed a Strouhal number scaling (based on burner diameter and jet exit velocity) for this peak frequency [12,13]. Noting the shortcomings of these Strouhal number scalings, others [14,15] have suggested that this frequency is kinetically controlled.…”
Section: Introductionmentioning
confidence: 98%
“…Also, an attempt is made to minimize the usual uncertaintie s as s ociated with external flameholder s. Premixed flames have also been studied here, under otherwise identical conditions, with the intention of having a ready and meaningful basis of comparison with non-premixed flames. Some of these results were presented earlier (Kumar 1974). Those experiments, done in a hard-walled bay, have now been repeated in an anechoic chamber, and the two results are compared.…”
Section: Introductionmentioning
confidence: 88%
“…The Experimental Details As described earlier (Kumar 1974), the details are as follows. Figure 1 shows the simple apparatus constructed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation